Analysis of Competitive Strategies to Improve Business Performance of Aerospace Training and Education Institute Gemilang Training Center - Satria Tirtayasa (IHSA Institute, 2022)
The Angkasa Gemilang Aviation Education and Training Institute is an aviation training and education institution that was established in 2008. Its students come from high school graduates or the equivalent. From 2008 to 2015 the number of students continued to increase, but from 2016 to 2020 the number of students continued to decline by more than 50%. This is what underlies the research, namely to formulate the right competitive strategy. This study uses a quantitative descriptive method with interviews and direct questionnaires to both internal and external sources. Analysis of the input stage is carried out with the IFE, EFE, CPM matrix, the matrix stage with the IE Matrix, Grand Strategy, SWOT, and the decision stage with the QSPM matrix. Then the implementation of the chosen strategy with the Short-Term and Long-Term Logical Framework is carried out. The strategy analysis concludes that the company's position is in quadrant I with an aggressive strategy to the promotion of market selection by aggressively and more broadly utilizing information and communication technology optimally.